A case of pancreaticoduodenal artery bleeding after laparoscopic right colectomy requiring open hemostasis - Rika Ono; Tetsuro Tominaga; Takashi Nonaka; Yuma Takamura; Kaido Oishi; Toshio Shiraishi; Shintaro Hashimoto; Keisuke Noda; Terumitsu Sawai; Takeshi Nagayasu (Surgical Case Reports, 2024)
Abstract Background Pancreatic and duodenal-related complications after right colectomy carry a higher risk of mortality. Case presentation A 64-year-old woman underwent laparoscopic right colectomy for a laterally spreading tumor in the cecum. On postoperative day 10, she experienced sudden hematemesis. Contrast-enhanced computed tomography (CT) of the abdomen showed a large amount of hemorrhage in the stomach, but no obvious extravasation. In addition, free air was observed near the duodenal bulb. Despite blood transfusion, vital signs remained unstable and emergency surgery was performed. The abdomen was opened through midline incisions in the upper and lower abdomen. A fragile wall and perforation were observed at the border of the left side of the duodenal bulb and pancreas, with active bleeding observed from inside. As visualization of the bleeding point proved difficult, the duodenum was divided circumferentially to confirm the bleeding point and hemostasis was performed using 4-0 PDS. The left posterior wall of the duodenum was missing, exposing the pancreatic head. For reconstruction, the jejunum was elevated via the posterior colonic route and the duodenal segment and elevated jejunum were anastomosed in an end-to-side manner. Subsequently, gastrojejunal and Brown anastomoses were added. Drains were placed before and after the duodenojejunal anastomosis. Postoperative vital signs were stable and the patient was extubated on postoperative day 1. Follow-up contrast-enhanced CT of the abdomen showed no active bleeding, and the patient was discharged home on postoperative day 21. As of 6 months postoperatively, the course of recovery has been uneventful. Conclusions We encountered a case of pancreaticoduodenal artery hemorrhage after laparoscopic right colectomy. Bleeding at this site can prove fatal, so treatment plans should be formulated according to the urgency of the situation.